2015
DOI: 10.1016/j.neuropsychologia.2015.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Relations between social-perceptual ability in multi- and unisensory contexts, autonomic reactivity, and social functioning in individuals with Williams syndrome

Abstract: Compromised social-perceptual ability has been proposed to contribute to social dysfunction in neurodevelopmental disorders. While such impairments have been identified in Williams syndrome (WS), little is known about emotion processing in auditory and multisensory contexts. Employing a multidimensional approach, individuals with WS and typical development (TD) were tested for emotion identification across fearful, happy, and angry multisensory and unisensory face and voice stimuli. Autonomic responses were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…Future studies would benefit from an investigation of the neurological and physiological responses to the biographical face stimuli used here, to further our understanding of the WS positive bias. Such research would extend existing findings (Haas et al, 2009; Jarvinen et al, 2015) and would indicate whether the bias for positive biographical faces reported here at the attentional level is replicated at the neural level, via amygdala and frontal lobe dysfunction, and the physiological level, via a lack of habituation to biographically trustworthy faces. Similarly, future research exploring the attentional processes underlying the WS positive bias would benefit from the simultaneous measurement of eye movements while conducting a dot-probe task.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Future studies would benefit from an investigation of the neurological and physiological responses to the biographical face stimuli used here, to further our understanding of the WS positive bias. Such research would extend existing findings (Haas et al, 2009; Jarvinen et al, 2015) and would indicate whether the bias for positive biographical faces reported here at the attentional level is replicated at the neural level, via amygdala and frontal lobe dysfunction, and the physiological level, via a lack of habituation to biographically trustworthy faces. Similarly, future research exploring the attentional processes underlying the WS positive bias would benefit from the simultaneous measurement of eye movements while conducting a dot-probe task.…”
Section: Discussionsupporting
confidence: 80%
“…Using skin conductance response measures, Jarvinen et al (2015) found that WS individuals exhibited a lack of habituation for happy faces, relative to controls matched on chronological age. This finding was paired with decreased arousal for fearful faces in the WS group, relative to controls.…”
Section: A Physiological Basis For the Positive Social Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormalities in auditory processing in WS seem to be restricted to the perception of negative affective vocalizations, such as scream or gasp ( 96 ). However, children with WS had no difficulty to recognize vocal emotions compared to controls ( 94 , 95 ). Emotional information can be transmitted via both visual (e.g., facial expressions and gestures) and auditory (e.g., affective prosody) channels.…”
Section: Resultsmentioning
confidence: 84%
“…Multisensory processing, a fundamental mechanism for disambiguating complex environmental signals [5], may contribute to a multitude of diseases and disorders if impaired. Previous reports have established compromised multisensory integration (MSI) in delayed motor development [2], moderately severe to severe cerebral palsy [6,7], intellectual disability [8,9], autism spectrum disorder [10,11], problems with attention including diagnosed attention de cit, hyperactivity disorder [12], sensory organ dysfunction [13], presence of sensory processing disorders [14]. Furthermore, as MSI has been implicated in language development [15,16] and learning disabilities e.g.…”
Section: Introductionmentioning
confidence: 99%